Instagram-Based Element Chemistry Poker Card Game in Improving Students' Critical Thinking - Putera Dwi Bagus Rendy Astid; Hadi Wiwin Puspita; Agustina Dea Adira (SHS Web of Conferences)
Learning media in chemistry subjects is needed so that students can better understand chemical materials that are very complex. Instagram-based Poker Chemistry Card game media as an alternative media in learning elemental chemistry. Critical thinking is a whole series of cognitive activities that are used by individuals in dealing with problems. This study aims to analyze the effect of applying the Instagram-based poker Chemistry Elements card game to increasing students' critical thinking. This media development research uses a quasi-experimental research method with a non-equivalent Pretest-Posttest Control Group Design type. This research was tested in class XI SMA using two classes with a total of 70 students. The test instrument was developed based on critical thinking indicators with a total of 10 questions. Critical thinking indicators used are basic clarification, basic support, inference, further clarification, strategy and tactics. The test data results were analyzed using a single ANCOVA with pretest as a covariate. The test results show that Ho is rejected which means there is a significant difference and influence in the application of Instagram-based chemical element poker cards on students' critical thinking abilities in elemental chemistry material. The results of this research confirm that Instagram-based elemental chemistry poker card media can improve students' critical thinking skills in elemental chemistry material.